Effect of Supplementation of Antioxidant Sericin in Semen Extender on Post-Thaw Sperm Quality, Oxidative Status and Fertility of Jaffarabadi Buffalo Bull Semen - Vijyeta, Hardipsinh P; Kavani, Fulabhai S; Vagh, Arshi A; Solanki, Gajendrasingh B; Vala, Karsan B; Singh, Vivek K; Dham, Arjan J (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present investigation was undertaken on semen of six Jaffarabadi buffalo bulls, aged 6-8 years (n=6x6=36 ejaculates) with an  objective of determining the influence of different concentrations of Sericin, viz., 0.0% control (T0), 0.25 % (T1), 0.50 % (T2), 0.75 %  (T3), 1.0 % (T4) in AndroMed® extender on the quality of sperm parameters, oxidative status and fertility of cryopreserved semen.  The semen samples were evaluated at pre-freeze (on dilution) and post-thaw stages. The pre-freeze sperm motility, viability, plasma  membrane integrity, acrosome integrity and total antioxidant capacity of semen were significantly (p
Keywords: Cryopreservation; Fertility; Jaffarabadi buffalo semen; Oxidative markers; Sericin